Development of Inquiry-Based Student Worksheets (Lkpd) on The Material of Changes in the State of Substance to Improve Critical Thinking Abilities - Ayu Saniah Sihotang; Andina Halimsyah Rambe (Educazione: Journal of Education and Learning, 2025)
This study aims to develop inquiry-based Science Student Worksheets (LKPD) on the material of changes in the state of matter to improve critical thinking skills of fifth-grade students of SDS Islam Azizi Medan. The background of this study is based on the low involvement of students and suboptimal critical thinking skills in science learning which is still dominated by lecture methods and the use of textbooks. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of fifth-grade students of SDS Islam Azizi Medan as well as validators of material experts, media experts, and learning experts. Data collection techniques used observation, questionnaires, documentation, and critical thinking ability tests. The results showed that the developed LKPD obtained a validation percentage of material experts of 90%, media experts of 90%, and learning experts of 90% with a very valid category. The results of the practicality of LKPD obtained an average percentage of 90% with a very practical category. The effectiveness of the LKPD is seen from the increase in the average pretest score of 58 to 86 in the posttest with an N-Gain value of 0.68 in the moderate category. The use of inquiry-based LKPD can increase students' learning activity and critical thinking skills in the indicators of interpretation, analysis, evaluation, and inference. Thus, the inquiry-based science LKPD is suitable for use as a teaching material to improve the critical thinking skills of elementary school students.